The Effect of Content Marketing on Decision Making of Graduate School of Business Administration in Thailand - Thanisorn Rojanadilok; Viroj Daraviroj (Journal of Education and Vocational Research, 2019)
This study was an investigation of undergraduate student use content marketing to decision to study in the graduate school of business administration in Chonburi, Thailand. The graduate education prepares students for research in professional program.In2019, there is a lot of connection among people through the use of information and can leverage social media marketing to enhance their programs. The performance of the workplace offers the persons who graduate in graduate education level. The educators need content marketing to decision making to study in graduate school of business administration in Thailand. This study was qualitative research by In-depth interview of 30 bachelor degree’s people which three people from each district in Chonburi, Thailand. The research has significant in the website’s content, and facebook’s content of graduate school of business administration. The factors influence to apply to study in master and doctoral degree were the graduation programs, cost of attendance, graduation degree, location of the campus, university reputation, alumni, and current students opinion to graduate school.